Business Process Innovation To Enhance Operational Efficiency (Case Study: Pt. Triton Global Maritim) - Nabil, Rifqi Ihsan; Mirzanti, Isti Raafaldini (UNIVED Press, 2026)
This study investigates how PT Triton Global Maritim, an Offshore Support Vessel (OSV) company in Indonesia, addressed rising additional costs caused by inefficiencies in its document handling processes within the Procurement and Logistics (PNL) division. To resolve this, the company initiated the development of Resource Planning (ERP) system. The research applied Design Thinking to identify user problems and Agile Scrum to implement ERP features iteratively. A combination of Design Thinking and Agile Scrum methodologies was applied: Design Thinking was used to identify user problems through focus group discussions with the PNL user and interviews with the director, while Agile Scrum guided the iterative development and testing of the ERP prototype. The results indicate that the newly developed ERP system updates significantly improve process performance, reducing document lead time by 307% to 800% compared to the previous system. These findings confirm that combining Design Thinking and Agile Scrum provides an effective framework creating an internal ERP solution to optimize organizational efficiency and decision-making within the company.